Correlation Between the Grade of Hydronephrosis with Surgical Outcomes After Ultrasound-guided Supine Percutaneous Nephrolithotomy: A Retrospective Observational Study - Tiopan NAPITUPULU; Yosua HARDJA; Martin SUSANTO; Grace Dumamawarni HUTAHAEAN; Ika RIANTRI; Hendra SUTAPA; Yusuf RACHMAN; Andre Marolop Pangihutan SIAHAAN (Medeniyet Medical Journal)
Objective: The preferred therapy for staghorn stones and large kidney stones is percutaneous nephrolithotomy (PCNL). Ultrasound-guided PCNL has definite advantages over fluoroscopy-guided PCNL. Preoperative characteristics are essential to assess better surgical outcomes. The goal of this study was to analyze the correlation of hydronephrosis with surgical outcomes after ultrasound-guided supine PCNL. Methods: A retrospective study was conducted at Doris Sylvanus General Hospital. Data of the patients was obtained from hospital records. Hundred and five patients underwent ultrasound-guided PCNL in the supine position from August 2020 to August 2022. Data were analyzed using SPSS 16.0. Results: The presence of hydronephrosis was 85 (80.95%), which consisted of Grade I 15 (14.30%), Grade II 25 (23.80%), Grade III 28 (26.70%), and Grade IV 17 (16.20%). In our study analysis, complications occurred in 16 patients (15.23%). Grade I complications of the Clavien-Dindo classification was of in 4 cases, 11 cases of grade 2 complications, and 1 patient died. The statistical result was the relationship between grade hydronephrosis and the grade of complication using the modified Clavien-Dindo system. We found a p-value of 0.207 (>0.05), and there is no statistically significant relationship p=0.382 and r=-0.086 was a negative correlation. There is also no statistically significant relationship between hydronephrosis and stone clearance with p=0.310. Conclusions: The use of ultrasonographic guidance PCNL has been reported as a safe and effective procedure for the management of large renal stones. In this study, there was no correlation or signification between hydronephrosis and surgical outcome after ultrasound-guided supine PCNL.